Psychometric properties of the Patient Health Questionnaire-4 among Hong Kong young adults in 2021: Associations with meaning in life and suicidal ideation - Fong, Ted C. T.; Ho, Rainbow T. H.; Yip, Paul S. F. (Frontiers in Psychiatry, 2023)
Background: Young adults in Hong Kong are subject to elevated psychological distress given the societal stressors such as civil unrest and COVID-19 pandemic and suicide is a leading cause of death among them. The present study aimed to evaluate the psychometric properties and measurement invariance of the 4-item Patient Health Questionnaire-4 (PHQ-4) as a brief measure of psychological distress and its associations with meaning in life and suicidal ideation (SI) in young adults. Methods: A mobile survey recruited a large and random sample of 1,472 young adults (Mean age = 26.3 years, 51.8% males) in Hong Kong in 2021. The participants completed the PHQ-4 and Meaning in Life Questionnaire – short form (MLQ-SF) for presence of meaning in life (MIL), SI, COVID-19 impact, and exposure to suicide. Confirmatory factor analysis was conducted to examine the factorial validity, reliability, and measurement invariance of PHQ-4 and MLQ-SF across gender, age, and distress subgroups. Multigroup structural equation model evaluated and compared the direct and indirect effects of latent MIL factor on SI via latent PHQ-4 factor across distress groups. Results: Both MIL and PHQ-4 supported a 1-factor model with good composite reliability (Ω = 0.80 – 0.86) and strong factor loadings (λ = 0.65 – 0.88). Both factors showed scalar invariance across gender, age, and distress groups. MIL showed significant and negative indirect effects (αβ = -0.196, 95% CI = -0.254 to -0.144) on SI via PHQ-4. PHQ-4 showed a stronger mediating role between MIL and SI in the distress group (Δ = -0.146, 95% CI = -0.252 to -0.049) than the non-distress group. Higher MIL predicted higher likelihoods of help-seeking (Odds ratios = 1.46, 95% CI = 1.14 - 1.88). Conclusions: The present results support adequate psychometric properties in terms of factorial validity, reliability, convergent validity, and measurement invariance for the PHQ-4 in young adults in Hong Kong. The PHQ-4 demonstrated a substantial mediating role in the relationship between meaning in life and SI in the distress group. These findings support clinical relevance for using the PHQ-4 as a brief and valid measure of psychological distress in the Chinese context.